Systemic therapy of androgenic alopecia - I. N. Kondrakhina; A. N. Mareeva (Vestnik Dermatologii i Venerologii, 2017)
The article describes the literature sources related to the efficacy of systemic therapy of androgenic alopecia in female and male.